2018
DOI: 10.1002/tox.22533
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and effects of the neonicotinoid thiamethoxam on Scaptotrigona bipunctata lepeletier, 1836 (Hymenoptera: Apidae)

Abstract: The neonicotinoid thiamethoxam is widely used in different agricultural crops, and it has a spectrum of action against insects, affecting both pests and pollinators, such as bees. In this study, the effects of exposure to sublethal concentrations of thiamethoxam on stingless bees Scaptotrigona bipunctata were evaluated. Foragers bees were exposed to the insecticide and subjected to genetic biochemical, histochemical, and morphological analyses after 24, 48, and 72 h of ingestion. Analysis of isoenzyme esterase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 70 publications
2
30
1
3
Order By: Relevance
“…Regarding the toxic effect of thiamethoxam at sublethal concentrations, the results of this study agree with previous reports showing reduced lifespans of other stingless bee species 42,43 . Thus, this study supports the notion that neonicotinoid insecticides are more detrimental to stingless bees at sublethal concentrations than N. ceranae infections.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the toxic effect of thiamethoxam at sublethal concentrations, the results of this study agree with previous reports showing reduced lifespans of other stingless bee species 42,43 . Thus, this study supports the notion that neonicotinoid insecticides are more detrimental to stingless bees at sublethal concentrations than N. ceranae infections.…”
Section: Discussionsupporting
confidence: 92%
“…Clearly, honey bees are negatively impacted by N. ceranae and neonicotinoid insecticides alone or in combination, but we know very little about how they affect other bee species, particularly in the tropics. Few studies have shown that stingless bees, social bees lacking stingers, are negatively impacted by neonicotinoid insecticides 42 , 43 and can be vectors of N. ceranae spores 28 , 29 , but we do not know if N. ceranae is capable of infecting and proliferating in them or if they could be adversely affected if exposed to both stressors, something likely to occur in natural and managed ecosystems. This is important, not only because stingless bees play a significant role as pollinators of flowering plants in the tropics, but also because several species of stingless bees have been managed for honey and cerumen production since ancient times, constituting a source of income for indigenous populations in the Americas 44 , 45 .…”
Section: Introductionmentioning
confidence: 96%
“…Inúmeros trabalhos verificaram alterações citotóxicas promovidas por pesticidas nas abelhas (JACOB et al, 2015;MOREIRA et al, 2018;MARQUES, LIMA, BERNARDES, 2020). A espécie A. mellifera, é empregada como organismo modelo em pesquisas, principalmente, as direcionadas para detecção de efeitos a compostos tóxicos (JACOB et al, 2015).…”
Section: Efeitos Da Exposição De Abelhas Aos Pesticidasunclassified
“…Os efeitos in vitro de tiametoxam em larvas de A. mellifera foram identificados na avaliação morfológica e imunocitoquímica dos cérebros de abelhas expostas, apresentam células reduzidas e morte celular precoce nas células dos lobos ópticos (TAVARES et al, 2015). Testes em laboratório avaliaram também o neonicotinoide tiametoxam em abelhassem-ferrão Scaptotrigona bipunctata, permitiram observar alterações no intestino médio incluindo desprendimento do epitélio da lâmina basal, além de desorganização epitelial e alterações morfológicas significativas nas células digestivas (MOREIRA et al, 2018).…”
Section: Efeitos Da Exposição De Abelhas Aos Pesticidasunclassified
See 1 more Smart Citation